HUBUNGAN ANTARA ADVERSITY QUOTIENT, SELF EFFICACY DAN KEBIASAAN BELAJAR DENGAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS X KECANTIKAN SMK NEGERI SE-KECAMATAN UMBULHARJO - Shinta Ika Ardyanti; Esti Harini (Universitas Sarjanawiyata Tamansiswa, 2015)
This research intent to know relationship: (1) adversity quotient with learned achievement, (2) self efficacy with learned achievement, (3) study habits with learned achievement, (4) are jointly between adversity quotient, self efficacy and study habits with math learned achievement in tenth grade students of beauty skill program Vocational Middle School at Umbulharjo District. This study was expost facto.Â This study population was all student in tenth grade of beauty skill program Vocational Middle School at Umbulharjo District totaling 209 students. The sampling technique used was a cluster random is sampling than sample was 62 students. Technique of data collecting used the technique to measure adversity quotient, self efficacy and study habits, and documentation technique to measure student achievement. The data analysis technique used is the descriptive statistical analysis and correlation analysis. The result showed that: (1) There is a positive and significant relationship between adversity quotient with math learned achievement student with a correlation of 0,352. (2)There is a positive and significant relationship between self efficacy with math learned achievement student with a correlation of 0,466. (3) There is a positive and significant relationship between study habits with math learned achievement student with a correlation of 0,442. (4) Taken together there is a positive relationship between adversity quotient, self efficacy and study habits with math learned achievement student with a correlation of 0,609. Based on these results, it was concluded that students learned achievement is influenced by adversity quotient's factor, self efficacy and study habits.